Odpowiedzi

2009-09-07T20:31:14+02:00
Y=1/2x-3/2
4x+y=2
4x +1/2x - 3/2 = 2
9/2x =7/2
x=7/9
4*7/9+y=2
y = 2-28/9
y= - 10/9
2009-09-07T20:48:37+02:00
Układ równań
y=1/2x -3/2
4x + y =2

y=x/2-3/2
4x+y=2

y=x/2-3/2
4x + (x/2+3/2) = 2

y=x/2-3/2
4x + (x-3)/2=2

y=x/2-3/2
(8x+x-3)/2 = 2

y=x/2-3/2
9x-3 = 4

y=x/2-3/2
9x=4+3

y=x/2-3/2
x=7/9

y=7/9/2-3/2 = 7/9*1/2-3/2 =7/18-3/2 = (7- 9*3)/18
y=(7-27)/18 = -20/18 = -10/9 = - 1 1/9
2009-09-07T21:03:39+02:00
Y=1/2x -3/2
4x + y =2



y=x/2-3/2
4x+y=2



y=x/2-3/2
4x + (x/2+3/2) = 2




y=x/2-3/2
4x + (x-3)/2=2


dalej...
y=x/2-3/2
(8x+x-3)/2 = 2




y=x/2-3/2
9x-3 = 4




y=x/2-3/2
9x=4+3



y=x/2-3/2
x=7/9


a to wynosi:
y=7/9/2-3/2 = 7/9*1/2-3/2 =7/18-3/2 = (7- 9*3)/18
y=(7-27)/18 = -20/18 = -10/9 = - 1 1/9